2013
DOI: 10.1002/art.37954
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Grade 1 Gray‐Scale Ultrasound Findings in Wrists and Small Joints to the Assessment of Subclinical Synovitis in Rheumatoid Arthritis

Abstract: Objective. To investigate the clinical relevance of grade 1 findings on gray-scale ultrasound (GSUS) of the joints in patients with rheumatoid arthritis (RA).Methods. We examined the wrists and small joints of 100 patients with early or established RA and 30 healthy controls, using GSUS and power Doppler ultrasound (PDUS). Independent clinical assessment of all joints for tenderness and swelling according to the European League Against Rheumatism examination technique was performed. Joints with grade 1 finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 27 publications
4
65
1
2
Order By: Relevance
“…Low level of imaging activity was defined less strictly, allowing gradually 1 to maximum 2 joints or tendons with positive synovitis or tenosynovitis, binary graded (GS and PD global scores for binary evaluation of synovitis and tenosynovitis≤1 or ≤2). GS and PD synovitis detected with US in patients in remission according to clinical scores was named subclinical synovitis [20]. GS and PD tenosynovitis detected with US in the same group of patients was named in our study subclinical tenosynovitis.…”
Section: Us Examinationmentioning
confidence: 74%
“…Low level of imaging activity was defined less strictly, allowing gradually 1 to maximum 2 joints or tendons with positive synovitis or tenosynovitis, binary graded (GS and PD global scores for binary evaluation of synovitis and tenosynovitis≤1 or ≤2). GS and PD synovitis detected with US in patients in remission according to clinical scores was named subclinical synovitis [20]. GS and PD tenosynovitis detected with US in the same group of patients was named in our study subclinical tenosynovitis.…”
Section: Us Examinationmentioning
confidence: 74%
“…The authors do not mention the sides were the PD was found but they published an US image with a PD signal from the dorsal side of the joint. Probably the same explanation is valuable for the grade 1 synovitis, due to its incipient pathologic vascularization: in the presence of grade 1synovitis the PD signal was much frequent detected in the dorsal side (28.1%) comparing with palmar side (3.7%) [12]. Also, Witt et al [24] found in patients with newly diagnosed rheumatoid arthritis (RA) more pathologic findings in grey-scale US from the palmar approach and more frequent PD signals from the dorsal approach of the finger joints.…”
Section: Discussionmentioning
confidence: 90%
“…For these reasons the term of "synovitis" should be reserved only for cases with proved inflammation by using color/power Doppler [9]. The correct interpretation of the grade 1 grey-scale US aspect of the MCP (normal or minimal synovial thickening) is one of the most debated subjects [9][10][11][12] concerning US criteria for early inflammatory arthritis.…”
mentioning
confidence: 99%
“…Because of the uncertainties that still exist when integrating US into clinical decision making, and because our patients had severe longstanding disease, we adopted a cautious approach defining US remission as PDUS 0 in all joints, even though the significance of grade 1 change is uncertain and can occur in patients with osteoarthritis (31) and a proportion of healthy volunteers (32). We elected to make treatment decisions on the basis of PDUS only and ignored grayscale changes because their significance in later RA remains uncertain (33). Following anti-TNF dose reduction, 8 patients were identified as having subclinical synovitis despite DAS28 remission using US at routine …”
Section: Discussionmentioning
confidence: 99%